Perceptions associées à l'intégration sociale, à la capacité à réussir et au soutien à l'engagement académique d'étudiants de 1re année dans le cadre d’un programme d’allègement de cursus à l’ULiège - Laurent Leduc; Céline Tonus; Pascal Detroz (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Although legally accessible to any first-year student who requests it, reduced program remains an uncommon and poorly documented practice. At the Faculty of Veterinary Medicine of the University of Liège, first-year students who sign an agreement for a reduced program after the January examination session are offered specific remedial activities and follow-up.Our study focused on the 39 students who completed this program during the 2017-2018 and 2018-2019 academic years. Semi-directed interviews were conducted with 21 voluntary students, and a thematic qualitative analysis was performed in order to investigate positive and negative perceptions of various dimensions of this programme supporting integration, motivation and engagement.We were particularly interested in perceptions about (i) quality of interactions with peers and staff; (ii) pedagogical approaches and learning activities in the different courses; and (iii) expectancy or perceived self-efficacy compared to actual performance at the end of the program.Although our study focused on a program with a currently small number of participants, it highlights the recurrence of positive declarations and perceptions related to engagement in the context of reduced program. We also observed a positive sense of the ability to succeed, not always associated with success, but often linked with improved performance. The results of the study are presented as likely to form a basis for reflection when setting up a remedial programme for a small student population.